Exploration of Bioactive Compounds Potency of Extract Namanereis sp. (Polychaeta: Annelida) as an Antibacterial Agent Against Escherichia coli and Staphylococcus aureus - Delianis Pringgenies; Endah Sari; Widianingsih Widianingsih; Anuwat Nateewathana (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
Namanereis sp. belongs to class Polychaeta, a group of main benthic community in marine ecosystems. The purpose of this study to determine the potential of bioactive compounds from Namanereis sp. extract as an antibacterial agent and to determine its extract content through Gas Chromatography–Mass Spectrometry (GC-MS) analysis. Samples of Namaneries sp. were collected from Demak Waters, Central of Java. This research used experimental laboratory method. Samples were extracted with non-polar (N-Hexane), semi-polar (Ethyl acetate) and polar (Methanol) solutions. Different concentrations of extraction, i.e. 5, 10, 20, 40, 80, and 100 µg.disk-1. then were tested against pathogenic bacteria Escherichia coli and Staphylococcus aureus. The extract content analysis was obtained using the GC-MS method.  The results showed that Namanereis sp. extract had a potential as an antibacterial agent. The highest inhibition zone was seen in the fraction with ethyl acetate solvent at a concentration of 100%, namely 13±3.05 mm in E. coli and 14±3.04 mm in S. aureus, which then was analysed with GC-MS. Its results found 20 bioactive compounds in the extract. The five most dominant compounds determined by the highest peak were Dihydrojasmone (12.31%), Hexanoic acid (11.49%), Cholesterol (7.66%), Cyclohexanol (7.53%) and Isopropyl Palmitate (7.52%). The research concluded that Namanereis sp. possessed antibacterial potency and contained several bioactive compounds.